Dietary Habits Fluctuations after Immigration: A Focus on University Students Immigrants in the United Kingdom - Eva Njambi, Waithaka (International Journal of Scientific Research and Management (IJSRM), 2023)
As a result to the students’ migration to foreign countries, they are forced to adjust to the new host’s environment, culture and tradition. One major adjustment required is their diet. This study assesses actual dietary intake changes after students’ immigration to the UK. This study adopted the approach of a cross-sectional study design to collect quantitative data using a questionnaire. A sample size of 99 international students was selected. Snowball sampling was used in selecting the study’s participants. All data was quantitative hence analysed using the software Statistical Package for Social Sciences (version 26.0). Differences in consumption of the food items pre and post immigration were evaluated using t-test for related samples. The findings show that intake of foods perceived to be non-western such as nuts, fruits and vegetables, proteins such as beans, meat soup, fish and sausages  decreased while intake of fat rich highly processed foods perceived to be western such as chips, cheese, bacon, sausages and ham increased after immigration to the UK.